Modelling and evaluation of net ecosystem productivity and its driving factors in Inner Mongolia - Cui, Shengjie; Zhao, Shuixia; Li, Chao; Wu, Yingjie; Kolerski, Tomasz; Zhang, Mengmeng (Frontiers in Environmental Science, 2025)
Net ecosystem productivity (NEP) is a critical indicator for characterizing the carbon cycle dynamics within terrestrial ecosystems. This study employs six different combinations of methods for calculating Net Primary Productivity (NPP) and heterotrophic soil respiration Rh) to estimate monthly NEP values in Inner Mongolia from 2001 to 2021. The carbon flux observation data obtained through the eddy covariance method are used to validate and evaluate these combinations, and the best NEP estimation model combination is selected, and the spatiotemporal distribution patterns of NEP along with its primary driving factors are analyzed. Results show that: 1) The NEP estimates derived from MODIS NPP combined with the Global Soil Respiration Model (GSMSR) and Bond-Lamberty’s Rs-Rh relationship model exhibit a strong correlation with validated data; 2) The NEP in Inner Mongolia shows a significant increasing trend, with an annual average value of 168.73 gC·m−2·a−1, or 177.57 gC·m−2·a−1 when excluding barren. Forests, croplands, and grasslands are identified as the primary carbon sinks during the growing season, with average NEP values of 84.81, 46.41, and 32.95 gC·m−2·mth−1, respectively; 3) Precipitation is the dominant meteorological factor driving the spatiotemporal variations of NEP across the region, contributing 72.29% to NEP during the growing season. Additionally, over 80% of areas influenced by human activities exhibit a positive impact on NEP; 4) The interannual and growing season increases in NEP are primarily attributed to climate change and anthropogenic activities, which account for 57% and 66.3% of NEP variations, respectively. These effects are particularly pronounced in the eastern forested regions and central grasslands of Inner Mongolia. The findings of this study provide valuable insights for regional carbon sink management and ecological environment protection.